Determination of Insulation Properties of Functional Clothing Using Core Body Temperature Gradients as Quantification Parameter - Bulut, Jonathan; Janta, Marius; Senner, Veit; Kreuzer, Johannes (Procedia engineering, 2013)
Increasing quality requirements for functional sports- and work wear make their development more demanding as complex interaction between human physiology and clothing is to be taken adequately into account. Previous test designs, often based on subjective perceptions, make a convincing comparison difficult. Material-specific laboratory tests only offer limited validity regarding effects on physiological and ergonomic properties. Principal objective of the study is to compare two different types of down jackets with respect to their effect on core body temperature during physical activity and inactivity. Both jackets were filled with different lining, one with chemically modified down called “QuixDown” (QD), the other one with conventional down (CD). A climatic chamber test with two activity sessions and a break in between was performed. Subjects were physically active on a bike ergometer at moderate level. A total of n = 26 (12m, 14f) healthy and physically active subjects between 18 and 35 years of age were randomly divided into control (CG) and treatment group (TG). TG was equipped with the QD, control group with the CD jacket. To ensure identical loading intensity for the test the individual anaerobic threshold of each subject had been determined in a pretest. Each person was equipped with an in-ear thermometer for measuring the core body temperature at the acoustic meatus. With QD jacket the subject's core body temperature dropped less during the break between both activity sessions than when wearing the CD jacket (p < 0.05, ω2 = 0.124). No statistical significance could be shown in gender (p = 0.22, ω2 = 0.02) and interaction jacket/gender (p = 0.56, ω2 ≈ 0). The chemically modified down insulation seems to offer better thermal insulation than conventional down.